Magnetic field controlled C60-TEMPO catalyst for the oxidation of alcohols. (21st January 2020) - Piotrowski, Piotr; Żukrowski, Jan; Kaim, Andrzej
Abstract : TEMPO functionalized C60 fullerene phosphonic acid was grafted onto the surface of magnetic IONPs. The resulting catalyst was employed in oxidation of various primary and secondary alcohols to their corresponding aldehyde or ketone analogues. Abstract : TEMPO functionalized C60 fullerene bearing phosphonic acid anchoring group was successfully synthesized and characterized using cyclic voltammetry and the following spectroscopic techniques: ESI-MS, NMR, ESR, and FT-IR. The obtained fullerene derivative was grafted onto the surface of oleic acid stabilized magnetic iron oxide nanoparticles using the ligand exchange reaction. The resulting nanocomposite material was characterized by means of TEM, EDX, XPS, Mössbauer spectroscopy, and TGA. Subsequently, the obtained catalyst was employed for the selective oxidation of various primary and secondary alcohols to their corresponding aldehyde or ketone analogues and its activity was examined. The results showed high activity of the described catalyst; the reported procedure enables the oxidation of selected alcohols with chemoselectivity and good yields at mild conditions. Moreover, the magnetic properties of the presented catalyst allow easy control and removal of the catalyst using external magnetic field. High stability of the catalyst along with a simple removal method and no disposal problems, and allowing multiple reuse without noticeable loss of efficiency demonstrates the potential value of the reported catalyst in the application of primary and secondary alcohol oxidation.